Application of Accounting Information Systems in Micro, Small and Medium Enterprises - Nuraini, Reny; Gardi, Bayar; Darmawan, Didit (Bulletin of Science, Technology and Society, 2024)
Micro, Small and Medium Enterprises (MSMEs) are a form of business that is growing rapidly. The ability of MSMEs to survive difficult economic downturns has led various parties to develop MSMEs. The government helps by providing policies that benefit MSME entrepreneurs. The weakness of MSMEs that disrupts business continuity is the absence of information from the accounting system. The absence of special business reports makes it difficult for MSME owners to analyse accounting information systems. Implementation of an Accounting Information System (AIS) in MSMEs has a significant impact on operational efficiency and business sustainability. This article identifies the benefits, challenges and potential solutions associated with implementing AIS in MSMEs. The benefits of AIS include more efficient management of financial transactions, improved decision making, and compliance with tax and reporting requirements. However, MSMEs also face challenges such as limited resources and data security. Solutions to these challenges include support from governments, educational institutions, and business organizations through training, mentoring, and access to necessary technology. With the right support, MSMEs can harness the full potential of SIA to improve their business performance and maintain sustainability in a competitive business environment.